The articulation of national integration in Malaysian English print media - Mohd Nasir, Nora; Govindasamy, Subramaniam; Hasan Khan, Mahmud (UM Press, 2008)
This is a study about the discursive construction of national integration (Bangsa Malaysia) as perceived by two Malaysian English news dailies: The New Straits Times and The Star. National integration, in Malaysia and elsewhere is largely a political concept constructed by the political leaders and/ or visionaries appeared in the country. It is an ‘empty signifier’ which develops around a ‘lack.’ Media as ideological state apparatus may help constructing the notion of national integration. This chapter would analyse the interpretation of national integration in Malaysia as perceived by editorials and opinion editorials published in two English language newspapers in the country.